Scalable Manufacturing Method for Model Protein-Loaded PLGA Nanoparticles: Biocompatibility, Trafficking and Release Properties - Selin Akpinar Adscheid; Marta Rojas-Rodríguez; Salma M. Abdel-Hafez; Francesco S. Pavone; Marc Schneider; Akif E. Türeli; Martino Calamai; Nazende Günday-Türeli (Pharmaceutics)
Background and Objectives: Drug delivery systems (DDSs) offer efficient treatment solutions to challenging diseases such as central nervous system (CNS) diseases by bypassing biological barriers such as the blood–brain barrier (BBB). Among DDSs, polymeric nanoparticles (NPs), particularly poly(lactic-co-glycolic acid) (PLGA) NPs, hold an outstanding position due to their biocompatible and biodegradable qualities. Despite their potential, the translation of PLGA NPs from laboratory-scale production to clinical applications remains a significant challenge. This study aims to address these limitations by developing scalable PLGA NPs and evaluating their potential biological applications. Methods: We prepared blank and model-protein-loaded (albumin–FITC and wheat germ agglutinin-488 (WGA-488)) fluorescent PLGA NPs using the traditional double-emulsion method combined with the micro-spray-reactor system, a novel approach that enables fine particle production enabling scale-up applications. We tested the biocompatibility of the NPs in living RPMI 2650 and neuroblastoma cell lines, as well as their trafficking and uptake. Release kinetics of the encapsulated proteins were investigated through confocal microscopy and in vitro release studies, providing insights into the stability and functionality of the released proteins. Results: The formulation demonstrated sustained and prolonged protein release profiles. Importantly, cellular uptake studies revealed that the NPs were not internalized. Furthermore, encapsulated WGA-488 protein retained its functional activity after release, validating the integrity of the encapsulation and release processes. Conclusions: The proof-of-concept study on NP manufacturing and an innovative drug trafficking and release approach can bring new perspectives on scalable preparations of PLGA NPs and their biological applications.